Monthly oral ibandronate therapy in postmenopausal osteoporosis: 1-year results from the MOBILE study. - Miller, P; McClung, MR; Macovei, L; Stakkestad, J; Luckey, M; Bonvoisin, B; Reginster, J; Recker, R; Hughes, C; Lewiecki, E; Felsenberg, D; Delmas, P; et al. (2005)
UNLABELLED: Once-monthly (50/50, 100, and 150 mg) and daily (2.5 mg; 3-year vertebral fracture risk reduction: 52%) oral ibandronate regimens were compared in 1609 women with postmenopausal osteoporosis. At least equivalent efficacy and similar safety and tolerability were shown after 1 year. INTRODUCTION: Suboptimal adherence to daily and weekly oral bisphosphonates can potentially compromise therapeutic outcomes in postmenopausal osteoporosis. Although yet to be prospectively shown in osteoporosis, evidence from randomized clinical trials in several other chronic conditions shows that reducing dosing frequency enhances therapeutic adherence. Ibandronate is a new and potent bisphosphonate with antifracture efficacy proven for daily administration and also intermittent administration with a dose-free interval of >2 months. This report presents comparative data on the efficacy and safety of monthly and daily oral ibandronate regimens. MATERIALS AND METHODS: MOBILE is a 2-year, randomized, double-blind, phase III, noninferiority trial. A total of 1609 women with postmenopausal osteoporosis were assigned to one of four oral ibandronate regimens: 2.5 mg daily, 50 mg/50 mg monthly (single doses, consecutive days), 100 mg monthly, or 150 mg monthly. RESULTS: After 1 year, lumbar spine BMD increased by 3.9%, 4.3%, 4.1%, and 4.9% in the 2.5, 50 /50, 100, and 150 mg arms, respectively. All monthly regimens were proven noninferior, and the 150 mg regimen superior, to the daily regimen. All monthly regimens produced similar hip BMD gains, which were larger than those with the daily regimen. All regimens similarly decreased serum levels of C-telopeptide, a biochemical marker of bone resorption. Compared with the daily regimen, a significantly larger proportion of women receiving the 100 and 150 mg monthly regimens achieved predefined threshold levels for percent change from baseline in lumbar spine (6%) or total hip BMD (3%). All regimens were similarly well tolerated. CONCLUSIONS: Monthly ibandronate is at least as effective and well tolerated as the currently approved daily ibandronate regimen in postmenopausal osteoporosis.